Predictors for 12-month long-term outcome in patients with obsessive-compulsive disorder: The influence of duration of untreated illness and age at onset. (December 2021) - Zheng, Huirong; Luo, Guowei; Yao, Siyu; Wang, Shibin; Guo, Guangquan; Quan, Dongming; Gao, Junling
Abstract: Background: It remains unknown whether the duration of untreated illness (DUI) may play a critical role in clinical improvement of patients with obsessive-compulsive disorder (OCD). Using a relatively large sample of subjects with OCD, this study investigated the potential impact of the DUI on patients' clinical course and long-term treatment response. Methods: Two hundred and seven patients with OCD recruited by the OCD outpatient clinic of our university hospital participated in the study. The sample was divided into two groups according to the median DUI (DUI≤3 years and DUI >3 years). Patients were treated with selective serotonin reuptake inhibitors or venlafaxine for 48 weeks in open-label conditions. Treatment response and other clinical variables were analysed. Results: The total sample showed a mean (SD) DUI of 4.07 (3.5) years, and the mean (SD) illness duration was 6.27 (6.5) years. More than half of the patients had not been treated before (56.5% for OCD). With a median of 3 years as cutoff DUI, response rates were found to be significantly higher in subjects with a short DUI (p < 0.001). Regression analyses showed that a short (≤3 years) DUI and later age at onset predicted better response and higher Y-BOCS scores percentage changes at the endpoint of 48 weeks (β = −1.11, p = 0.003). In addition, there was no correlation between DUI and age of onset in the total patients (r = −0.13, p＞0.05). Conclusions: This preliminary study suggests associations between a shorter duration of untreated OCD and favourable long-term outcomes, and a longer DUI with a worse clinical course.